(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The Aptian-Albian Scisti a Fucoidi, widespread in the Umbrian-Marchean Basin (Central Italy), consist of a pelagic cyclic varicolored sequence of marls, marly limestones and "black shales". A core was drilled through this formation at Piobbico (Marche) and a detailed biostratigraphic investigation based on calcareous nannofossils was undertaken.